Optimizing fuel break management for core habitat protection against wildfires in the northern Great Basin - Nguyen, Dung; Wei, Yu; Belval, Erin J.; Young, Jesse D.; O'Connor, Christopher D.; Dunn, Christopher J.; Calkin, David E. (Ecological informatics, 2025)
In many fire-prone landscapes, protecting ecological values is an important objective of wildfire management. Here, we develop a mixed integer programming model for managing a network of linear fuel breaks to minimize wildfire impacts on the sagebrush (Artemisia spp.) core habitats in the northern Great Basin. The model uses simulated wildfires for 20,000 fire seasons, calibrated to historical fire occurrence data from 2006 to 2020. It coordinates treated fuel breaks to create opportunities to contain each simulated fire. Multiple treatment options with fuel break widths of 30 to 122 m are examined to facilitate effective suppression and prevent breaching by fires with flame lengths between 0.6 and 2.4 m. Both fires' burned areas and fuel breaks' treatment areas cause direct losses to the sagebrush core habitats. Our model was tested by constraining the direct habitat loss from treatments to within 0 to 8910 ha, repressing two extreme scenarios with no fuel break treatment or treating all fuel breaks at 122-m width. Model results highlight the importance of treating linear fuel breaks in the northern Great Basin, which can reduce the expected core habitat loss to wildfires by up to 38 % compared to the no-treatment scenario. More extensive treatment would cause diminishing returns, with no further reduction to core habitat loss to wildfires once treatment-related habitat loss exceeds 5346 ha. Our further analyses of the spatial fuel break layout solutions and their tradeoffs offer region-specific insights to support decision making. However, the model formulation is flexible for customizations to support broader applications in other fire-prone landscapes with different wildfire management objectives and requirements. •The model uses wildfire simulation to optimize fuel break management within a landscape.•Linear fuel breaks are managed with varying width options to facilitate wildfire containment.•Tradeoffs in ecological impacts from both fuel break management and wildfire are examined.•Test cases reveal insights for management and planning decisions.